Caracterisation Sedimentologique Et Mineralogique Des Formations Tertiares Du Bassin Onshore De La Region D’abidjan, Cote d’Ivoire - Jean Claude N’zi; Mamadou Toure; N’goran Jean-Paul Yao; Rachelle Affouet Kouassi; Zeli Bruno Digbehi; Kouamé Aka (European Scientific Journal, ESJ, 2018)
Analyzes carried out on 262 cuttings samples from two boreholes located in the coastal sedimentary basin of Abidjan (south-west of the lagoon fault) were aimed at the paleoenvironmental determination of tertiary-age deposits. Indeed, these sedimentological analyses allowed the characterization of the lithological nature of the formations encountered by AB and BM drilling. They also helped to determine the origin of the sedimented material as well as the hydrodynamic conditions that governed the placement of the various deposits. Moreover, the deposits medium of the studied formations was revealed. The formations consist of an alternation of sands and sandy clays in the AB drilling and essentially glauconous clays for BM drilling. In the clay intervals, there is a weak presence of calcium carbonates on the whole of the two boreholes. The sands analyzed are of different granulometric grades (very coarse, coarse, medium and fine) according to the intervals. This, therefore, shows the different variations in the energy of the current that transported the sediment. From a facies point of view, the granulometric facies is dominant in the study area, indicating the variation in watercourse competence during sedimentation. Mostly sub-angular to sub-rounded quartz grains suggest a relatively distal proving source while their shiny blunted appearance evokes an aquatic environment. The sediments of these wells are therefore sands of fluviatile origin, deposited in a shallow marine environment.